2011
DOI: 10.1007/s12032-011-9862-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a is down-regulated in gastric cancer and regulates cell proliferation and apoptosis

Abstract: Aberrant expression of microRNA-146a (miR-146a) has been reported to be involved in development and progression in various types of cancers, but its role in gastric cancer has not been fully elucidated. The purpose of this study was to investigate the levels of miR-146a expression and its function in human gastric cancer. Quantitative real-time polymerase chain reaction was used to detect the levels of miR-146a expression in gastric cancer tissue samples and cell lines. The cell growth rate of MKN-45 gastric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 23 publications
2
57
0
1
Order By: Relevance
“…This result is consistent with a demonstrated role of miR-146a in other cancers, such as pancreatic and breast cancers, where it inhibits cancer progression and invasion (8,26,33). A recent report also showed a positive correlation of miR-146a expression with the survival time of gastric cancer patients (25). Furthermore, the overexpression of miR-146a inhibits the proliferation and survival of breast, prostate, and pancreatic cancer cells through the downregulation of other targets in these cells, including ROCK1, EGFR, and MTA-2 (8,33,34).…”
Section: Discussionsupporting
confidence: 90%
“…This result is consistent with a demonstrated role of miR-146a in other cancers, such as pancreatic and breast cancers, where it inhibits cancer progression and invasion (8,26,33). A recent report also showed a positive correlation of miR-146a expression with the survival time of gastric cancer patients (25). Furthermore, the overexpression of miR-146a inhibits the proliferation and survival of breast, prostate, and pancreatic cancer cells through the downregulation of other targets in these cells, including ROCK1, EGFR, and MTA-2 (8,33,34).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, Kim et al (11) also indicated enhanced miR-146a level in gastric cancer. However, recently, Hou et al (28) reported different expression of miR-146a in gastric cancer tissues. They found that 36 of 43 gastric cancer tissue samples (84%) showed decreased expression of miR-146a.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer (GC) is the second cause of cancerassociated death and the fourth most widespread tumor worldwide [4,5]. The development of GC involves various factors, including oncogenes and tumor suppressors.…”
Section: Introductionmentioning
confidence: 99%